Of scheme paradigmatic for matrix epistemological: systematizing new levels of analysis - Silva, Régis Henrique dos Reis; Sànchez Gamboa, Sílvio (Universidade Estadual de Campinas, 2014)
At the moment there is a significant increase in scientific production sciences share (education, physical education and especial education) in terms of quantity, its quality becomes questionable. We evaluate the continued study of this production and what has been the contribution of scientific research in the process of analysis, criticism, and finding solutions to problems faced by areas of this science and its links with broader social issues. Accordingly, in order to contribute to the debate political-epistemological and improvement of the epistemological critique of the action sciences, presented in this text, the genesis and development of the Matrix Epistemological while instrumental theoretical-philosophical analysis of scientific science action.